Analytical Method Development and Validation of Stability Indicating Rp-Hplc Method for the Simultaneous Estimation of Abacavir and Dolutegravir - lakshmi, G.Sai sri; I, Somasundaram (Journal of Neonatal Surgery, 2025)
Special, effective high pressure liquid chromatography method has been developed for the simultaneous quantification of Abacavir and Dolutegravir.By using Waters HPLC e-2695 quaternary pump with a PDA detector of 2998 instrument the chromatographic separation of Abacavir and Dolutegravir was achieved on the column of Inertsil ODS150X4.6mm, 3.5µ using an isocratic elution with a buffer containing 0.1percentformic acid and acetonitrile at a rate of 30:70 as a mobile phase with a flow rate of 1 ml/min at ambient temperature. A detector wavelength of 236 nm utilizing the PDA detector were given in the instrumental settings. The linearity was studied between the concentration range of 30-450 µg/ml of Abacavir and 5-75 µg/ml of Dolutegravir were injected.The plotted calibration curves were linear with a regression coefficient of R2> 0.999, indicates that the linearity was with in the limit. As a part of method validation the parameters like specificity, linearity, accuracy, ruggedness, robustness were determined and the results were found to be within the allowable limit. The method developed was found to be applicable to routine analysis and to be used for the measurement of both active pharmaceutical ingredients (i.e, Abacavir and Dolutegravir).Validation of the proposed method was carried out according to an International Conference on Harmonization (ICH) guidelines